Information Communication Technology on Human Resource Development for Environmental Welfare - M Fikri Akbar; Indah Nur’Aini; Edy Fitriawan Syahadat (Saburai International Journal of Social Sciences and Development, 2018)
Development of human resources is very basic. The relationship between performance at the organizational level and the national level, as well as investment in human resource development is tangible and persuasive. Thus, developing thoughts about the prospects and role of communication in human resource development becomes an important part. The methodology used to comply with this paper is through literature study from various literatures.Communication is a prerequisite for information transfer. Economic underdevelopment is often correlated with limited access to information and learning facilities. The ability to communicate and transfer information and capacity is vital to building a knowledge economy that ensures survival in a global setting. Thus, the availability and development of human resources is important in the context of the socio-economic conditions of the country and the communication of information technology is an important asset for global competitiveness.Besides, information and communication technology is utilized to maintain the environment by managing and monitoring the energy. Therefore, qualified and competent human resource who could create proper application to facilitate society can maintain environmental welfare such as save energy, reduce emission gas, and so on.Effective and quality communication is the core of all HR development. Understanding of communication is important to improve human resources as social capital. The development of human resources in information and communication technology is important for the ability of the people of a nation to promote global competitiveness and become one of the factors of progress of a nation in international arena.